P-244 Role for Sphingosine-1 Phosphate Receptor-3 (S1P3) in the Modulation of Innate/Adaptive Immune Cell Responses; Potential Therapeutic Target for IBD. (February 2017) - Tyler, Christopher; Rivera-Nieves, Jesus
Abstract : Background: Sphingosine-1 Phosphate (S1P) is a membrane-derived lysophospholipid, responsible for a variety of functions in the regulation of the cardiovascular, nervous, and immune systems. Signalling induced by S1P can be facilitated by 5 different sphingosine phosphate receptors, denoted S1P1-5. S1P3, while being involved primarily in regulation of vascular function, has recently been revealed to modulate several immune cell processes. Such processes include the chemotaxis of numerous innate immune cell subsets, endocytosis by dendritic cells and induction of T cell responses, and proinflammatory cytokine production by neutrophils. However, little is known of S1P3 modulation of cellular immune responses in the context of intestinal immunity and inflammation. In addition, while evidence has shown a role for S1P3 in the regulation of innate immune responses, little is known of the regulation of adaptive immune responses, particularly that of T cells. Study Aims: This study aims to identify a role for S1P3 in mediating immune responses in the intestine, and its involvement in inflammatory pathways during IBD. In addition, the role of S1P3 in modulating innate and adaptive immunity, and differences in expression and function between acute and chronic inflammatory models were investigated. Methods: Murine models of acute inflammation (DSS-induced colitis), and chronic inflammation, (TNFΔARE model of chronic ileitis) were utilised in this study. S1P3 knock-out mice and S1P3-mCherry reporter mice were used to investigate the expression and functional roles of S1P3 via flow cytometry and immunofluoresecence. Results: By crossing S1P3 reporter mice with TNFΔARE mice we observed significant upregulation of S1P3 mRNA in inflamed terminal ilea by real-time RT-PCR, and S1P3 protein by flow cytometry. This upregulation was observed not only in innate immune subsets such as DCs, but also on adaptive immune subsets including T and B cells. We also observed significant S1P3 expression on CD31 negative/GP38 positive follicular stromal cells, which are greatly amplified in the chronically inflamed terminal ilea of TNFΔARE mice. In addition, a model of DSS-induced colitis identified that S1P3 knock-out mice are protected from disease-induced weight loss as compared to their wild-type counterparts (n = 10, 10% weight loss for S1P3 KO mice versus 0% weight loss for wild-type mice, P < 0.05). Conclusions: Increased expression of S1P3 in cells isolated from mice with chronic ileitis suggests that S1P3 may play a prominent role during inflammatory processes. Given the observed protection from acute DSS-induced colitis in S1P3 KO mice, S1P3 may also be important for the function of innate immune cells during acute inflammation. Ongoing studies will attempt to elucidate the exact mechanism and cellular subsets responsible for this protection, as well as a potential protective role of S1P3 during chronic intestinal inflammation. Furthermore, with the clinical development of S1P receptor agonists, modulation of S1P3 utilising such therapies may present a potential therapeutic option for IBD.